2022
DOI: 10.2147/jmdh.s375724
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Differences Among Mildly Symptomatic and Asymptomatic Patients with Omicron Infection in 2022 in Shanghai, China

Abstract: Background An epidemic of the Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) began in March 2022, and over 600,000 cases were confirmed until early May 2022 in Shanghai, China. Data on Omicron infections are available in other countries, but the clinical features of patients in the Chinese population, especially in Shanghai, are still lacking. We collected data from a subset of asymptomatic and mildly ill patients to learn about the age and sex disparity of Omicron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Further research is required to understand the molecular and pathophysiological mechanisms underlying these gender differences in COVID-19 infection and severity. Comparison among age groups showed that the infection rate was lower among people over 50 years old, which is consistent with other studies ( 23 ). It may be related to the decline of immune function in aging individuals, which would result in less obvious symptoms and being classified as uninfected.…”
Section: Discussionsupporting
confidence: 92%
“…Further research is required to understand the molecular and pathophysiological mechanisms underlying these gender differences in COVID-19 infection and severity. Comparison among age groups showed that the infection rate was lower among people over 50 years old, which is consistent with other studies ( 23 ). It may be related to the decline of immune function in aging individuals, which would result in less obvious symptoms and being classified as uninfected.…”
Section: Discussionsupporting
confidence: 92%
“…There are reports that [ 5 ] in 2020, patients in shelter hospitals in Wuhan had different mental health problems, with the incidence of anxiety and depression among these patients at about 72.73% and 71.72%, respectively [ 3 ]. In a recent survey of patients in shelter hospitals in Shanghai, 261 cases (97.4%) were detected with psychological symptoms, among which the detection rates of depression, neurasthenia, fear, obsessive-anxiety, and hypochondria were 80.6%, 69.8%, 89.6%, 75.4%, and 41%, respectively [ 23 ]. In contrast, the depression rate of the general population in the non-pandemic period was 5.9% [ 24 ], and anxiety 5.3% [ 25 ], thus showing a very heightened rate of both depression and anxiety after infection.…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron variant has spread rapidly worldwide, inducing a pandemic in Shanghai in March 2022 (1). Thus far, at least 32 mutations have been identified in the spike protein, resulting in high transmissibility and immune escape (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%